A Noncatalytic Approach to Hetaryl‐Annulated 1, 2, 4‐Thiadiazine‐1, 1‐dioxides. (5th August 2013) - Cherepakha, Artem; Kovtunenko, Vladimir O.; Tolmachev, Andrey; Lukin, Oleg
Abstract : A set of synthetic procedures was developed to yield functionalized pyrido‐, pyrimido‐, and thiazo‐annulated thiadiazine‐1, 1‐dioxides on a preparative scale. In all cases the thiadiazine‐1, 1‐dioxide ring closure was carried out through a reaction of hetaryl‐sulfonyl chlorides with amidines under mild noncatalytic conditions. In the case of 2‐chloropyridine‐3‐sulfonyl chloride derivatives and 2, 4‐dichlorothiazole‐5‐sulfonyl chloride open‐chain sulfonylated amidine intermediates were isolated and then subjected to thecyclization step. The reaction with 2, 4‐dichloropyrimidine‐5‐sulfonyl chloride gave rise to the corresponding thiadiazine‐1, 1‐dioxides in one‐pot. Similarly, a reaction of 2‐chloropyridine‐3‐sulfonamide with lactime ethers proceeded in one‐pot readily giving the corresponding thiadiazine‐1, 1‐dioxides. Remaining chlorine atoms on the prepared hetaryl‐annulated benzothiadiazine‐1, 1‐dioxides readily undergo aromaticnucleophilic displacement reactions serving thus as additional variation points for the design of biologically potent compounds. Abstract :